Islamic Banking Development, Monetary Policy, and Economic Growth: A Panel Moderated Regression Approach for Selected Islamic Countries - Nurafifah Zein; Riskiana Elina (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to analyze the influence of Islamic banking developments and monetary indicators on economic growth in nine Muslim-majority countries, with inflation as a variable This study uses a quantitative method with Moderated Regression Analysis (MRA) estimation panel data using secondary data sourced from SESRIC and the World Bank for the 2013–2023 period. Total Assets (TA) has a significant positive effect on economic growth, while Total Funding and Equity (TFE) and Broad Money (BM) have a significant negative effect. The variables of Sukuk Holdings (SUK), Exchange Rate (ER), and inflation do not show a direct influence on GDP. The moderation results show that inflation acts as a quasi-moderator in the TA and TFE variables, but does not become a moderator in BM, SUK, and ER. These findings confirm that price stability is an important prerequisite for the transmission of monetary policy and the intermediation function of Islamic banking to contribute optimally to the real economy. This research contributes novelty by including inflation as a moderation variable in the context of cross-border Islamic finance, as well as providing practical implications for monetary authorities to strengthen macro stability in the development of the Islamic finance industry.